Metagenomics exploring the effect of recombinant rice based on lotus seed starch-broken rice flour on intestinal flora in rats - ZHANG,Yu (2022)
Abstract High fat diet may cause obesity, diabetes, atherosclerosis, hypertension, hyperlipidemia and other diseases, and even mortality. The recombinant rice based on mixing lotus seed starch and broken rice flour was used to feed high-fat diet rats, and its effects on body weight and organ index were determined. The changes of intestinal flora in rats were studied by macrogenomic technology, and the effects of lotus seed starch-broken rice flour recombinant rice (LSBR) on intestinal flora in rats were discussed. The results showed that adding enough LSBR could effectively inhibit the weight gain of rats, reduce the liver index from 0.3498 to 0.2836, and the kidney index from 0.0079 to 0.0072. The reduction of intestinal flora abundance and diversity caused by high-fat diet were improved, the relative abundance ratio of Firmicutes/Bacteroidete was reduced from 11.04 to 2.17, while the relative abundance of beneficial bacteria was increased.